Increased incidence of tuberculosis in patients of systemic sclerosis on dexamethasone pulse therapy: A short communication from Kashmir - Ahmad Qazi; Shah Iffat; Nauman Qazi; Sameem Farah; Sultan Javaid (Wolters Kluwer Medknow Publications, 2008)
Background: Systemic sclerosis is a multi-systemic autoimmune disorder affecting predominantly the skin, lungs, gut and kidneys. Purpose: To report the increased incidence of tuberculosis in patients of systemic sclerosis on dexamethasone pulse (DP) therapy. Methods: Forty-seven patients of systemic sclerosis were included in the study. After taking a complete history and doing a detailed physical examination, the patients were submitted to a battery of investigations including complete hemogram(CBC) with erythrocyte sedimentation rate (ESR(F)), Chest X-ray CXR (PA view) Mantoux test and urine analysis. CBC, ESR and urine examination was done monthly and CXR were repeated six-monthly. Findings: Seven patients on DP therapy developed genitourinary tuberculosis. Four had pulmonary tuberculosis. One patient developed tubercular lymphadenitis, one patient succumbed to miliary tuberculosis. Conclusion: There is an increased incidence of tuberculosis amongst patients of systemic sclerosis on DP therapy. Limitation of the Study: There was no control group of systemic sclerosis patients not on DP therapy to rule out the confounding effect of the disease per se predisposing to tuberculosis as all our patients as a matter of routine were put on steroid pulse. Also, the increased incidence of tuberculosis was detected incidentally while on monthly follow-up.